PENGARUH PRAKTIK PENGELOLAAN PENGETAHUAN TERHADAP KINERJA ORGANISASI RETAIL X: THE INFLUENCE OF KNOWLEDGE MANAGEMENT PRACTICES ON THE PERFORMANCE OF RETAIL ORGANIZATION X - Cahyadi, Angelica; Caroline, Angela (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
Knowledge is a valuable asset for companies and good knowledge management is the basis for creating a sustainable company or organization that can survive changes and global competition. Knowledge management practice has four dimensions which aim to manage existing knowledge in the organization to be used effectively and efficiently so that later it can improve organizational performance. This study aims to measure how influential knowledge management practices are on organizational performance in the parent company Retail X (one of the leading companies in the retail industry in Indonesia). In this study, survey methods were used and the type of research used in this study was causal. Data collection techniques used by distributing questionnaires and interviews. The data analysis technique was carried out with quantitative data analysis techniques. The result of the research conducted indicate that : the knowledge management practice variable had a positive influence of 19.8% on organizational performance.